الاستثمار السياحي في الجزائر - حشروف جمال (المسيلة, 2022)
e abundant tourism potentials that it possesses, from a beautiful nature and civilized and cultural diversity, by enacting, issuing and approving a set of laws that pursue a policy of incentive and encouragement for investment in the tourism field while trying to overcome all obstacles and difficulties facing tourism investment in Algeria. keywords : Keywords: tourism, investment, ingredients, obstaclesتسعى الجزائر بمختلف جهودها إلى استغالل المقومات السياحية الوفيرة بة وتنوع حضاري وثقافي، وذلك بـسن التي تمتلكها ، من طبيعة خالا وإصدار واعتماد مجموعة من القوانين المنتهجة لسياسة تحفيزية وتشجيعية لالستثمار في المجال السياحي مع محاولة تذليل كل العراقيل والصعوبات التي يواجها اإلستثمار السياحي في الجزائر. الكلمات المفتاحية: السياحة، اإلستثمار، المقومات، العراقيل.
Keywords: الاستثمار - السياحة -الجزائر